Identification of tendency to temporomandibular joint dysfunction progression based on morphometry - Mirza, Р. О.; Biloklytska, Г. Ф. (Actual Dentistry, 2024)
Actuality. The temporomandibular joint diagnosis includes the computer tomography analysis. This research method is extremely common, and as a rule, it is used during the stages of orthodontic treatment of gnathological patients and is actually more accessible in comparison with magnetic resonance imaging (MRI). The information obtained during the TMJ computer tomograms analysis, while making up an orthodontic plan, orthopedic treatment, can affect the sequence of occlusal rehabilitation stages. The aim. To determine the morphometric parameters of the TMJ structure in which dysfunction accompanied by limited opening of the mouth occurs most often by means of analysing computer tomograms. Materials and methods. The width of the glenoid fossa and condylar head inclination were measured on computer tomograms in 91 subjects with limited mouth opening due to temporomandibular joint dysfunction. A general clinical examination was carried out, which included identification of the dominant side of chewing, previously existing clicking in the temporomandibular joint, which was revealed during the interview. Results. The largest number of examinees with temporomandibular joint dysfunction due to the limited mouth opening, had a width of the condylar head from 3.5–4.4 mm to 7.5–8.4 mm condylar head inclination angle from 53 to 72° (47.2%), and the smallest from 4.5–5.4 mm to 11.5–12.4 mm at an condylar head inclination angle from 85 to 93° (18.6%). Unilateral type of chewing was found in 41 (45%) of the examined, and clicking in the temporomandibular joint, which existed before the appearance of jamming, was confirmed by interviewing of 39 (42.8%) patients. Conclusions. The maximum width of temporomandibular joint, at which the condylar head inclination angle from 53 to 72° is detected on TMJ computer tomograms is 8.4 mm within patients with temporomandibular joint dysfunction, which is determined by the presence of limited opening of the mouth. Keywords: limited mouth opening, temporomandibular joint, computer tomography.